Optimal control and state observer for a robotic manipulator with three degrees of freedom - Luz Junior, José Adenilson Gonçalves (2018)
This work presents the modeling and simulation of a robotic manipulator robot with three degrees of freedom by considering its structures with rigid behavior. The concepts of kinematics for the mathematical deduction and the Lagrangian mechanics were applyed to obtain the dynamic models of the manipulator and the DC actuators with are considered as permanent magnet motors. Due to the nonlinearities and dynamics characteristics, both the states observer and the controler used were based on State Dependet Ricatti Equation (SDRE). The simulations made for constant performance parameters demonstrated the effectiveness of the optimal control applied to the manipulator and to the chosen DC actuator models. The applications of trajectories to the manipulator enrich the applicability of the project and the results obtained with the techniques chosen show his efficiency.